New combinations in Hawaiian Drosophila and Scaptomyza (Diptera: Drosophilidae) - Magnacca, Karl N.; O’grady, Patrick M. (Zootaxa, 2008)
The present paper transfers eight species from the genus Drosophila to the genus Scaptomyza based on characteristics of the male genitalia. One species, Scaptomyza (Titanochaeta) canuta (Hardy) new combination, fits within the concept of the subgenus Titanochaeta. The remaining seven taxa, S. improcera (Hardy) new combination, S. magnipalpa (Hardy) new combination, S. parva (Grimshawi) new combination, S. prolixa (Hardy) new combination, S. taractica (Hardy) new combination, S. totonigra (Hardy) new combination, and S. vinnula (Hardy) new combination, are included as unplaced species of Scaptomyza An additional species, Scaptomyza (Grimshawomyia) undulata (Grimshaw) new com- bination, is transferred from the subgenus Engiscaptomyza to Grimshawomyia based on morphological and molecular characters. An expanded key to the subgenera of Scaptomyza that includes these unplaced taxa is presented. In addition, Drosophila attigua Hardy & Kaneshiro is reduced to a junior new synonym of D. sharpi Grimshaw.